Understanding Ambiguity in Knowledge, Value and Institutional Structure: A Case Study of Chinese Open Network Community - Yao Jin (Jurnal Studi Pemerintahan)
Being a space for organizations to realize their value, it is necessary to minimize the structural Uncertainty of the virtual world. The analysis shows structural problems are the internal logical starting point of ambiguity in the net- work community and the underlying cause of gradual accumulation and pre- cipitation in social tension. Analyzing the structural stain from the dimension of knowledge, value, and institutional structure in the network community, multifarious ambiguity is found in Chinese network governance. A representative survey object is selected to understand Chinese network governance after COVID 2019. We choose The Changtze River Cloud com- munity on TikTok as the survey unit to analyze the public space management satisfaction ratio. Through theoretical discussion and case study, specific countermeasures are proposed, such as broadening the channels of expression, constructing cultural diversity in virtual space, and establishing clear specification standardization. It is expected that explicitness instead of ambiguity transmitted by authority can promote existing order to more open, creative, and satisfying institutional design for net citizens in virtual communities.